Multimedia courseware for visually impaired (MCVI) - Mohan, Arjunan (2011)
Multimedia Courseware for Visually Impaired (MCVI) is a speech recognition system that is aimed for visually impaired people who has low vision but have the speaking and listening ability.The objective of this system are to develop a simple and easy prototype of Speech Recognition learning application that reacts to speech commands and to help the visually impaired people or students in learning process through hearing,speaking and touching since hard learning materials are infective and required man power to guide them.The technique that had been used to develop this system was Linear Predictive Coding (LPC).The methodology that had been used was Rapid Application Development (RAD). This system enables visually impaired people or students to get accessed to computers and learn about things, lives an environment surroundings which to make them familiar and sense living and non-living things exist around them by hearing.This thesis discussed on the preparation and analysis that had been done in order to develop this system. A complete reference and research details had been inserted in this thesis.This thesis will be a quick reference to refer on the specification and requirements of the system.